2022
DOI: 10.1017/s1463423622000378
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on China’s primary care response to COVID-19: roles, limitations and implications

Abstract: This study focuses on the role of primary care in China’s response to COVID-19. A retrospective, reflective approach was taken using data available to one of the authors who led the national community response to COVID-19, first in Wuhan and then multiple cities in ten provinces/municipalities across the country. At the peak of the pandemic, primary care providers shoulder various public health responsibilities and work in close partnerships with other key stakeholders in the local communities. Primary care pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Host populations [ 43 ], weak capacity distribution of supplies, unavailability of quality services [ 42 , 44 ], and postponed routine care in PHC [ 33 , 45 ]. Cameroon, Congo, Mali, Nigeria, Iraq, Eastern Medicterrain Region (EMR), Libya, Yemen Constraints in service delivery Lack of trained workforces [ 46 ], failure of coordinated support overburdened hospitals [ 47 ], lack of primary care [ 45 ], high priority of hospitals services [ 48 ], health workforce workload [ 49 , 50 ], an increase of infections [ 15 ], the hotspot of epidemics but blind spot of PHC services [ 28 , 37 ], the spread of Ebola [ 43 ], increase of pre-existing diseases [ 34 ], reduced availability of services [ 45 , 51 ]. Italy, Australia, Brasil, Malawi, SSA, CAR, Ecuador Multiple impacts on building blocks of health systems Inadequacies of service provision [ 47 , 51 , 52 ], isolation, lockdown, restriction [ 53 , 54 ], collateral damage, interruption of service [ 53 , 55 58 ], post-disaster disease outbreaks [ 33 , 34 ], shortage of workforce and heavy workload [ 33 , 34 , 47 , 50 , 51 , 55 58 ], reliance on short term staff [ 46 ], poor data quality [ 56 ], poor resource coordination and readiness [ 29 , 52 , 59 ], unavailability of digital tools [ ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Host populations [ 43 ], weak capacity distribution of supplies, unavailability of quality services [ 42 , 44 ], and postponed routine care in PHC [ 33 , 45 ]. Cameroon, Congo, Mali, Nigeria, Iraq, Eastern Medicterrain Region (EMR), Libya, Yemen Constraints in service delivery Lack of trained workforces [ 46 ], failure of coordinated support overburdened hospitals [ 47 ], lack of primary care [ 45 ], high priority of hospitals services [ 48 ], health workforce workload [ 49 , 50 ], an increase of infections [ 15 ], the hotspot of epidemics but blind spot of PHC services [ 28 , 37 ], the spread of Ebola [ 43 ], increase of pre-existing diseases [ 34 ], reduced availability of services [ 45 , 51 ]. Italy, Australia, Brasil, Malawi, SSA, CAR, Ecuador Multiple impacts on building blocks of health systems Inadequacies of service provision [ 47 , 51 , 52 ], isolation, lockdown, restriction [ 53 , 54 ], collateral damage, interruption of service [ 53 , 55 58 ], post-disaster disease outbreaks [ 33 , 34 ], shortage of workforce and heavy workload [ 33 , 34 , 47 , 50 , 51 , 55 58 ], reliance on short term staff [ 46 ], poor data quality [ 56 ], poor resource coordination and readiness [ 29 , 52 , 59 ], unavailability of digital tools [ ...…”
Section: Resultsmentioning
confidence: 99%
“… CAR, Brazil, Malawi, Germany, Cameroon, SSA, Liberia, India Multisectoral actions Linkages between policymakers, community based organisations, NGOs, and private sector [ 13 ], community resilience, satisfaction, and confidence [ 16 , 30 ], Engaging stakeholders in planning [ 52 , 64 ], multisectoral actions for prevention of pandemic [ 54 ], community collaborations [ 30 , 70 ], multi-sectoral and comprehensive provincial pandemic and economy [ 56 ], “One Health” approach [ 29 , 63 ], multisectoral actions for non-health sector response [ 71 ], multisectoral coordination, integration of fragmented approaches [ 72 ]. Israel, Thailand, South Africa, Cuba Communication and partnership Strategic partnerships of international organisations [ 43 , 49 , 73 , 74 ], rebuilding coordination and communication networks, [ 27 , 47 , 67 ], humanitarian response, maintaining and outreach or mobile clinics [ 31 , 42 , 68 ], hospitality towards displaced populations [ 40 ], regional forums, institutions [ 26 , 72 ], global initiatives and cross-country lessons [ 71 , 75 ]. Sierra Leone, China, Italy, Japan, Yemen, Cameroon, Congo, Mali, Nigeria, EMR Use of digital tools systems shift to using new technologies and digital tools [ 26 , 45 , 49 , 50 , 76 ], digital consultation communication in remote consultations [ 53 , 55 , 68 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer studies, however, have used the event systems theory to investigate the impact of COVID-19 event strength on the mood and behavior of medical professionals, particularly in the PHC context. Due to the sudden nature and widespread impact of COVID-19, this pandemic has certainly posed considerable obstacles to the work and lifestyles of PHC medical professionals [33,34]. Therefore, we chose COVID-19 event strength as the main variable in our study to assess its impact on job burnout among this cohort.…”
Section: Event System Theorymentioning
confidence: 99%
“…A large number of studies conducted in healthcare settings had also demonstrated that job stress hinders the work engagement of healthcare professionals [52,69,70]. Following the outbreak of the COVID-19 pandemic, PHC medical staff encountered notable modi cations, especially in terms of workload, job content, psychological stress, and infectious practice environment [33]. Consequently, the immense stress and increased workload caused by the epidemic may negatively affect the work engagement of PHC providers, which, in turn, may have resulted in signi cant job burnout.…”
Section: The Chain Mediating Role Of Job Stress and Work Engagementmentioning
confidence: 99%